Balanço de energia em unidade de conservação no Pantanal mato-grossense por sensoriamento remoto - Danelichen, Victor Hugo de Morais (2015)
Changes in land use and occupation, as well as the preservation process of a protected area, change the energy balance. Thus, the growth of the vegetation and the reduction of surface albedo causing an increase in latent heat flow and consequently increased evapotranspiration. Thus, the aim of this study was to evaluate effects of the implementation of a protected area on the spatiotemporal patterns of the components of energy balance. The study was conducted at the RPPN SESC Pantanal, far 160 km of Cuiaba - MT, Brazil. Were acquired by the INPE, images TM Landsat 5 in the years 1984, 1999 and 2008. For the study of altimetry we used the Digital Elevation Model (DEM) obtained by SRTM radar. Rankings were performed supervised at all scenes obtained. For the realization of the energy balance was used SEBAL algorithm, which was validated with data obtained by the Bowen ratio method. The results showed that since the reservation of the implantation the most vegetated classes showed an increase, while areas of grassland and bare soil decreased. The analysis of SRTM data and vegetation indices showed that some vegetated classes occupy lowlands, while the arboreal vegetation, with emphasis on Cambarazal class, and occupy the highest regions. The albedo and surface temperature decreased throughout the study period, while the vegetation indices increased. The components of energy balance, except for the sensible heat flux increased throughout the study period. Evapotranspiration - daily (ET) showed an increase overall years studied. The SEBAL demonstrated high performance in the estimates of the components of energy balance, the balance of ET and daily radiation, according to the measurements in the field and studies in the same biome. The results show that increasing the vegetation indexes, the components of the energy balance and daily evapotranspiration and decreasing the albedo and the surface temperature over the whole study period, indicating that the vegetation developed after the creation and expansion the RPPN.